Application of house of risk to analyze supply chain risks in MSMEs (food processing industry) - Wahyuni, Nuraida; Trenggonowati, Dyah Lintang; Ibrahim, Maulana Malik; Anggraeni, Shanti Kirana; Ekawati, Ratna; Febianti, Evi (Universitas Sultan Ageng Tirtayasa, 2023)
Supply chain risk management plays a pivotal role for businesses, regardless of their size—be it large industries or Micro, Small, and Medium Enterprises (MSMEs). Even in MSMEs, supply chain risk management is crucial to mitigate potential risks stemming from various events. Consider BS, an MSME producing bread in Cilegon city, established in 2020, aspiring for market expansion. However, BS faces internal challenges such as fluctuating flour availability, recurring machine breakdowns twice a month, and consumer returns due to order discrepancies. Thus, this study aims to analyze supply chain risks to proactively prevent these recurrent events. The method employed here is the House of Risk. Through data processing, 32 risk events were identified by mapping supply chain activities based on the SCOR principle. From these events, 18 risk agents were derived, highlighting critical areas that require resolution. Employing a Pareto diagram, six priority risk agents have been identified for immediate resolution.